Factors affecting marginal integrity of class II bulk-fill composite resin restorations - Siavash Savadi Oskoee; Mahmoud Bahari; Elmira Jafari Navimipour; Amir Ahmad Ajami; Negar Ghiasvand; Ayda Savadi Oskoee (Tabriz University of Medical Sciences, 2017)
Background. Bulk-fill composite resins are a new type of resin-based composite resins, claimed to have the capacity to be placed in thick layers, up to 4 mm. This study was carried out to evaluate factors affecting gap formation in Cl II cavities restored using the bulk-fill technique. Methods. A total of 60 third molars were used in this study. Two Cl II cavities were prepared in each tooth, one on the mesial aspect 1 mm coronal to the CEJ and one on the distal aspect 1 mm apical to the CEJ. The teeth were divided into 4 groups: A: The cavities were restored using the bulk-fill technique with Filtek P90 composite resin and its adhesive system and light-cured with quartz tungsten halogen (QTH) light-curing unit. B: The cavities were restored similar to that in group A but light-cured with an LED light-curing unit. C: The cavities were restored using the bulk-fill technique with X-tra Fil composite resin and Clearfil SE Bond adhesive system and light-cured with a QTH curing unit. D: The cavities were restored similar to that in group C but light-cured with an LED light-curing unit. The gaps were examined under a stereomicroscope at ×60. Data were analyzed with General Linear Model test. In cases of statistical significance (P<0.05), post hoc Bonferroni test was used for further analyses. Results. The light-curing unit type had no effect on gap formation. However, the results were significant in relation to the composite resin type and margin location (P<0.001). The cumulative effects of light-curing unit*gingival margin and light-curing unit*composite resin type were not significant; however, the cumulative effect of composite rein type*gingival margin was significant (P=0.04) Conclusion. X-tra Fil composite exhibited smaller gaps compared with Filtek P90 composite with both light-curing units. Both composite resins exhibited smaller gaps at enamel margins.